Physico-Chemical Properties of Yellow Oleander (Thevetia peruviana) and their effects on the Qualities of Biodiesel - Nasirudeen, A. R.; Lasisi, D.; Balogun, L. A.; Eebo, A. J.; Ogunsola, F. O.; Adesope, A. J.; Ogundare, S. O.; Ola, F. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
This study investigated the effects of physico-chemical properties of Yellow oleander (Thevetia peruviana) on quality of biodiesel. The seeds were processed and extraction of oil was carried out using solvent extraction method. Biodiesel was produced from the extracted oil using trans esterification process. Physical and chemical properties of Thevetia peruviana biodiesel were determined using the ASTM standard test procedures. Results showed that the biodiesel contained little sulphur (3.0 mg/kg) and exhibited a high cetane number of 55 that exceeded the standard limit of 47 and 51 prescribed for EN 14214 and EN 590 respectively, which is a good indication of fuel’s ignition and combustion quality. Kinematic viscosity of the biodiesel at 40°C was 4.81 mm2/s, which was within the range specified by EN 14214. The density at 15°C was found to be 0.89g/cm3 which was well within the range specified by EN 14214. 0.16 mg/g of acid level was obtained for the bio-diesel, which conformed to the standard set by Calorific value of the biodiesel produced from Yellow oleander seed oil was obtained as 40.42 kJ/g which indicated good fuel properties such as density, ignition quality, viscosity, cetane number, heating value and flash point. Carbon residue of the biodiesel was 0.14 mass %. Quality of the biodiesel produced conform to biodiesel and petroleum diesel standards of EN14214 and EN590 respectively.